2012
DOI: 10.1515/cclm-2012-0005
|View full text |Cite
|
Sign up to set email alerts
|

γ′ Fibrinogen as a novel marker of thrombotic disease

Abstract: Abstractγ ′ Fibrinogen is an isoform of fi brinogen that normally constitutes about 7 % of total plasma fi brinogen, and arises from an alternative processing event in the γ chain mRNA. γ ′ Fibrinogen is a newly-emerging cardiovascular disease (CVD) risk factor that appears to have an independent association with CVD from that of total fi brinogen, which is itself a well-established CVD risk factor. γ ′ Fibrinogen shows a signifi cant association with coronary artery disease and myocardial infarction in at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 52 publications
2
41
0
1
Order By: Relevance
“…19 Fibrinogen g9 is thought to be related to cardiovascular disease (CVD) risk independent of total fibrinogen concentration. 11,20 Therefore, not only factors that affect g9 fibrinogen levels but also factors that could potentially influence the g9/total fibrinogen ratio should be determined.…”
mentioning
confidence: 99%
“…19 Fibrinogen g9 is thought to be related to cardiovascular disease (CVD) risk independent of total fibrinogen concentration. 11,20 Therefore, not only factors that affect g9 fibrinogen levels but also factors that could potentially influence the g9/total fibrinogen ratio should be determined.…”
mentioning
confidence: 99%
“…First, γ′ fibrinogen rises in the acute phase response [4], and higher levels strengthen clots by altering fibrin formation and structure and making clots resistant to fibrinolysis [4, 23, 24]. These properties may help explain why some studies have found higher γ′ fibrinogen associated with increased risk of atherothrombotic vascular disease [4, 5]. On the other hand, the γ′ isoform binds less strongly than does the γA isoform to platelets, possibly reducing platelet activation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a possible positive association of γ′ fibrinogen with atherothrombotic events in Framingham and several other epidemiological studies [4], studies of VTE have mostly reported the opposite association. For example, the Leiden Thrombophilia Study reported that having a FGG -H2 haplotype, which was strongly related to lower circulating γ′ fibrinogen, doubled the risk of VTE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of FIB concentration is often considered as a risk factor for cardiovascular disease and thrombosis (30). Besides, a number of studies have confirmed the predictive value of D-dimer levels for venous thromboembolism (16).…”
Section: In Colorectal Cancer Patientsmentioning
confidence: 98%